2019
DOI: 10.1159/000490546
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Study to Evaluate Respiratory Rate Using a Thermal Imaging Camera

Abstract: Background: Respiratory rate is a vital physiological measurement used in the immediate assessment of unwell children and adults. Convenient electronic devices exist for the measurement of pulse, blood pressure, oxygen saturation, and temperature. Although devices which measure respiratory rate exist, none have entered everyday clinical practice for acute assessment of children and adults. An accurate and practical device which has no physical contact with the patient is important to ensure readings are not af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The primary disadvantage of using this method is the cost of thermal and depth cameras and the camera operators. Although the price of these cameras is falling gradually, it remains substantially high [ 57 ]. The cost of the equipment is of course less expensive than methods such as CT and X-ray scanning, but still more expensive than other methods discussed further in this paper.…”
Section: Non-contact Sensing To Detect Covid-19 Symptomsmentioning
confidence: 99%
“…The primary disadvantage of using this method is the cost of thermal and depth cameras and the camera operators. Although the price of these cameras is falling gradually, it remains substantially high [ 57 ]. The cost of the equipment is of course less expensive than methods such as CT and X-ray scanning, but still more expensive than other methods discussed further in this paper.…”
Section: Non-contact Sensing To Detect Covid-19 Symptomsmentioning
confidence: 99%
“…Therefore, the classifier must be trained again using current data. A recent study [ 17 ] showed that adding automated thermal detection algorithms to contact methods improved RR detection compared with the contact method alone. However, the feasibility of the automated thermal model alone was not clarified.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 21 and 22 present results from a video dataset of 70 patients “during the immediate recovery after cardiac surgery” 21 with an average duration of 28.6 minutes. Elphick et al report results on 61 sleeping subjects (41 adults, 20 children) 23 . Although using healthy subjects under laboratory conditions, three published papers present results on more than 50 subjects, namely Fan and Li (65 subjects, one minute each) 24 , Cerina et al (60 subjects, five minutes each) 25 and Vieira Moco et al (54 subjects for model calibration, duration not reported) 26 .…”
Section: Survey Taxonomymentioning
confidence: 99%